Household solid waste generation rate and physical composition analysis: case of Sekondi-Takoradi Metropolis in the western region, Ghana - Nyankson, Eugene Atta; Fei-Baffoe, Bernard; Gorkeh-Miah, John (International Journal of Environment, 2015)
Sekondi-Takoradi Metropolis, one of the rapidly expanding cities of Ghana has been facing serious problems with solid waste management. This is mainly due to the lack of available information about the types and quantity of solid waste generation in the area. Hence, the objective of this study was to determine the rate of household solid waste generation and its composition in the aforesaid city. The methodology and procedures for this study were derived from the Standard Test Method for Determination of the Composition of Unprocessed MSW (ASTM D 5231-92). All samples were hand sorted into 6 waste categories (paper, plastic, organics, metals, glass, and other waste). The study revealed that by weight, organic wastes constitutes the largest proportion of household solid waste (38%) followed by 19% plastics, 7% papers, 4% metals, 4% glass and 28% other wastes (comprising of sand, stones, ash, inert substances). The rate of daily waste generation per capita in the low, middle and high income households were 0.27±0.19, 0.4±0.19 and 0.58±0.24 kg/cap/day, respectively. The study revealed that there is no waste treatment or recovery facility established within the metropolis hence no significant waste recovery and reuse activities exist. The study showed that more than 38 % of the waste generated in Sekondi-Takoradi Metropolis is decomposable organic matter that can be re-used through composting as well as 34% of the waste having recycling potential thereby considerably mitigating the solid waste problem. DOI: http://dx.doi.org/10.3126/ije.v4i2.12644 International Journal of Environment Vol.4(2) 2015: 221-235